Computational investigation of flows and pressure fields associated with spur gear meshing - Baydu, C. Al; Simmons, Kathy; Morvan, Herve (2014)
The efficiency of power transmission systems is increasingly targeted with a view to reducing parasitic losses and improving specific fuel consumption (SFC). One of the effects associated with such parasitic losses is the successive compression and expansion of fluid within the cavities between teeth of a meshing gear pair as they rotate. This process is cyclic and there are multiple cavities compressed and expanded at the same time.